Determinación de la calidad del agua para el uso de riego mediante bioindicadores en los ríos providencia y del Pongo, ubicados al este de la reserva ecológica los Ilinizas, perteneciente al cantón Latacunga, en la provincia de Cotopaxi. - Bautista Bautista, Omar Emerson (2023)
The present study was developed in the months of December 2022 and February 2023, in which the quality of water for irrigation of the Providencia and Pongo rivers was evaluated, using macro invertebrates as vindicators and biological indices (Biological Monito ring Working Party, Index Andean Biological and the Shannon Weaver biodiversity index); For this, six sampling points were determined (Low Point - Benito Pamba, Mid Point - Rodeo Loma, High Point - Chinchil, Low Point - Troje Guasha, Mid Point - Era Loma, High Point - Quilag). After taking samples and analyzing them, a total of 538 individuals of aquatic macroinvertebrates were identified in the Providencia River in the two months, in the Pongo River a total of 593 macroinvertebrates in the two months. Distributed in 14 families; By calculating the Biological Monitoring Working Party index of both rivers in the months of December and February, an Acceptable water quality was obtained. On the other hand, the Andean Biological Index shows a Regular water quality in the two tributaries, corresponding to the month of February. After calculating the Shannon Weaver biodiversity index in the Providencia River in the two months, an average of 2.08 was obtained, and in the Pongo River in the corresponding two months the average was 2.27, which express an average diversity . The results of the physical-chemical analyzes applied to the two rivers in the month of December showed that none of the evaluated parameters exceed the ranges of maximum permissible limits. Making the comparison with Table 4 of Annex I of Book VI of the TULSMA, of parameters of the quality levels of water for irrigation, in the month of February at the High Point of the Providencia Chinchil River the pH parameter exceeds the value of the allowed range , because the water is exposed to contaminants such as agricultural chemicals and pesticides, from crops in the area. With the results obtained, it was determined that the environmental quality of the water ranges from Regular to Acceptable, therefore if it is suitable for irrigation use.